UPAYA MENINGKATKAN KEMAMPUAN PASSING BAWAH BOLA VOLI MELALUI MODEL PEMBELAJARAN DIRECT INSTRUCTION PADA SISWA KELAS VI SDN SETONO 5 NGRAMBE - Andy Widhiya Bayu Utomo; Rendi Leonardo; Arief Nur Wahyudi (JGK (Jurnal Guru Kita), 2021)
Abstract : Efforts to Improve Volleyball Bottom Passing Skills Through the Direct Instruction Learning Model for Class VI Students at SDN Setono 5 Ngrambe. The purpose of this study was to see the results of improving the learning of volleyball underpassing techniques for sixth grade students of Setono 5 Ngrambe State Elementary School, Ngrambe District, Ngawi Regency through the Direct Instruction learning model approach. This research was conducted at SDN Setono 5 Ngrambe class VI consisting of 16 students. The type of this research is using Classroom Action Research (CAR) by using cycles of 2 (two) times where each cycle has two meetings. For data collection techniques than in this study, namely using observations (observations) and trials (tests). Based on observations and tests in the initial implementation, obtained 68.75% of students have not completed the implementation of learning or as many as 11 students. These results become a reference for researchers to implement improvements in the first cycle in order to improve student learning outcomes and complete student grades. The results of the first cycle obtained 9 students who are complete in carrying out learning or 56.25% of students who have completed. In the second cycle there was a very good increase as many as 14 students completed in carrying out volleyball lessons with the passing technique below or as many as 87.5% were completed. These results prove that the Direct Instruction learning model can improve or improve student learning outcomes in volleyball learning with the down passing technique as expected by the researchers.Keyword : Direct Instruction, Improves Down Passing, Volleyball Learning. Abstrak : Upaya Meningkatkan Kemampuan Passing Bawah Bola Voli Melalui Model Pembelajaran Direct Instruction pada Siswa Kelas VI SDN Setono 5 Ngrambe. Tujuan dari penelitian ini yaitu untuk melihat hasil dari peningkatan belajar teknik passing bawah bola voli terhadap siswa kelas VI Sekolah Dasar Negeri Setono 5 Ngrambe Kecamatan Ngrambe Kabupaten Ngawi melalui pendekatan model pembelajaran Direct Instruction. Penelitian ini dilaksanakan di SDN Setono 5 Ngrambe kelas VI yang tersiri dari 16 siswa. Jenis daripada penelitian ini yaitu menggunakan Penelitian Tindakan Kelas (PTK) dengan menggunakan siklus sebanyak 2 (dua) kali dimana setiap siklus masing-masing dua kali pertemuan. Untuk tehknik pengumpulan data dari pada penelitian ini yaitu mengunggkan pengamatan (observasi) dan uji coba (tes). Berdasarkan observasi dan tes pada pelaksanaan awal, diperoleh 68,75% siswa belum tuntas dalam pelaksanaan pembelajaran atau sebanyak 11 siswa. Hasil tersebut menjadi acuan peneliti untuk dilaksanakannya perbaikan di siklus I guna meningkatkan hasil belajar siswa dan ketuntasan nilai siswa. Hasil dari Pada siklus I diperoleh 9 siswa yang tuntas dalam melaksankan pembelajaran atau 56,25% siswa yang sudah tuntas. Pada siklus II terjadi peningkatan yang sangat baik sebanyak 14 siswa tuntas dalam melaksanakan pembelajaran bola voli teknik passing bawah atau sebanyak 87,5% yang tuntas. Hasil ini terbukti bahwa model pembelajaran Direct Instruction dapat memperbaiki atau meningkatkan hasil belajar siswa pada pembelajaran bola voli teknik passing bawah sesuai yang diharapkan oleh peneliti.Kata Kunci : Direct Instruction, Meningkatkan Passing Bawah, Pembelajaran Bola Voli.